Investigations into the freeze–thaw-induced alteration in microstructure and deteriorative responses of physico-mechanical properties of Himalayan rock - Sardana S.; Sinha R.K.; Verma A.K.; Singh T.N. (My University, 2025)
The freeze–thaw (FT) process plays a dominant role as far as the slope stability in the cold regions is concerned. The upper mountainous regions of the Himalayas are prone to recurrent FT. Himalayan rock is also used as building materials for the construction in cold hilly areas. Therefore, it becomes necessary to understand the behaviour of the Himalayan rock with respect to its deterioration prior to the construction of any engineering project. Rock samples of the Himalayan schist collected from Solang Valley in Himachal Pradesh, India were subjected to multiple FT conditioning in the laboratory. The microscopic damages and the degradation in physico-mechanical properties such as effective porosity, P-wave velocity and tensile and compressive strengths were observed on the rock specimens conditioned to 0th, 10th, 20th and 30th cycle of FT. The micro-photographs from the scanning electron microscope test reveal the widening of cracks due to FT. A significant gain in effective porosity and water absorption of about 33% and a reduction of about 11.5% in P-wave velocity, 28% in compressive strength and 40% in tensile strength was observed for rocks conditioned with 30 FT cycles. These results were further used in mathematical modelling to arrive at various coefficients, damage factor and the disintegration rate of Himalayan schist under the influence of FT. © 2022, Springer-Verlag GmbH Germany, part of Springer Nature.